Review of the Genus Entedon (Hymenoptera, Eulophidae, Entedoninae). IV. Revision of Ukrainian Species of hercyna Group - Gumovsky, A.V. (Вестник зоологии, 1999)
The Ukrainian species of hercyna group are revised. 7 species are recognized, 6 of them are new for the region. E. (E.) procioni Erdos, E. (E.) gracilior Walker, E. (£.) heyeri (Ratzeburg), E. (E.) abdera Walker, E. (E.) ukrainicus sp. n., E. (E.) ergias Walker, E. (E.) diotimus Walker are found in Ukrainian fauna. 5 new synonymies are established: E. molyb-daenus Erdos, 1944, E. urticarii Erdos, 1951, E. meliloti Askew, 1992 = E. [E.) procioni Erdos, 1944, E. loti Erdos, 1944 = E. (E.) diotimus Walker, 1839, E. nigritarsis Erdos, 1944 = E. (E.) abdera Walker, 1839. It is found that male paralectotype of E. longus BouCek, 1968 belongs to E. (E.) procioni Erdos, 1944. Diagnostic characters of the species group, the intraspecific variations and characters used for taxonomic purposes are discussed. Some new geographic records for other regions of Palearctic are given, key to the Ukrainian species is proposed.